Evolutionary dynamics of cetacean ERVs. - Jialu Zheng (1423381); Jianhua Wang (159545); Zhen Gong (292434); Guan-Zhu Han (155211) (2021)
( A ) Distribution of the genetic distance between 5’- and 3’ LTRs of complete ERVs in 315 cetacean ERV lineages. Blue and orange lines represent the distribution of the genetic distance between 5’- and 3’ LTRs of complete ERVs in the LTW and the SHS ERV lineages, respectively. The purple and green boxes represent 95% highest posterior distributions (HPD) of the genetic distance of introns between B . acutorostrata and H . amphibious (reflecting the divergence between cetaceans and hippopotamuses) and between B . acutorostrata and O . orca (reflecting the divergence between mysticetes and odontocetes) with dashed lines as the means. ( B ) Distribution of the genetic distance between 5’- and 3’- LTRs of complete ERVs in different cetacean ERV lineages under the SHS scenario. The purple and green boxes represent 95% HPD of the genetic distance of introns between B . acutorostrata and H . amphibious and between B . acutorostrata and O . orca , respectively, with dashed lines as the means.